Training on Social Media Marketing Strategies to Increase Competitiveness in SMEs - Rasyid, Ardiansyah; Clarissa, Clarissa; Chandra, Fredicko Decastro; Dharmawan , Jones Guna (International Journal of Social Science and Community Service, 2024)
Social Media Marketing is a marketing activity using social media sites such as Facebook, Twitter, Youtube, and so on. The activity partner is located in Jakarta. In its activities, it is known that partners have difficulties in the field of social media marketing. The activity aims to provide solutions to partners in improving their ability to compete and consistency in posting content. The activity method is carried out by conducting training on social media marketing, namely by presenting information and knowledge in determining social media marketing strategies. The advantages of this strategy are that the costs incurred are not too large, have broad access, besides that the operation is also quite easy. Training is conducted directly to the partner's place. With activities carried out by making PPT containing information that can be utilized to increase competitiveness using social media marketing has run smoothly. The output of activities in the form of publications to journals and IPR.